Method for obtaining a glazing
Patent Information
- Application Number
- CN202580018613.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-04-05
- Filing Date
- 2025-04-02
- Publication Date
- 2026-10-13
Smart Images

Figure CN122910216A_ABST
Abstract
Description
[0001] This invention relates to the field of window glass, and in particular to window glass for motor vehicles.
[0002] To ensure thermal insulation of a vehicle, it is known to coat one side of at least one glass sheet of the window glass with a thin stack, the thin stack particularly comprising one or more metal layers, especially a silver layer. Alternatively, the stack may comprise at least one transparent conductive oxide (TCO) layer. Such a stack has the property of reflecting infrared radiation, thereby limiting heat transfer between the vehicle exterior and the passenger compartment, resulting in reduced consumption for vehicle heating and air conditioning.
[0003] However, silver is easily corroded, and it is known that to prevent damage, a portion of the stack is removed from the periphery of the glass sheet—a method sometimes referred to as "edge clearing." The stack can also be removed in certain areas to allow electromagnetic waves to propagate well through portions of the window glass, thereby ensuring the proper functioning of onboard sensors and communication or navigation instruments. This creates a stack-free communication window.
[0004] To achieve this, mechanical methods such as abrasion can be used, but these methods may scratch or even weaken the glass. These mechanical methods are particularly relevant when the stack has previously deposited large glass sheets (e.g., approximately 6 x 3 m). 2 When used in conjunction with this method, the large glass sheet must subsequently be cut to obtain the final size of glass sheet for integration into the window glazing. Laser ablation methods are also known, but they are expensive and require laborious laser adjustment to avoid damaging the glass surface.
[0005] Alternatively, a mask can be deposited on areas where the stack is not intended to be deposited, and then removed once the stack has been deposited. This method is possible when the final window glass dimensions and the positioning of its edges are known during the deposition of the thin-layer stack. This is, for example, when the stack is deposited on a prototype larger than the final size of the glass sheet integrated into the window glass. Such a mask is, for example, a metal component or a water-soluble masking layer, which is subsequently washed off and, when removed, also allows for the removal of the overlying stack.
[0006] However, the latter method is not without its drawbacks. It turns out that complete removal of the masking layer may require time-consuming cleaning and expensive cleaning machines.
[0007] The purpose of this invention is to overcome these drawbacks by providing a more efficient and economical method.
[0008] Therefore, the object of the present invention is a method for obtaining window glass, comprising: depositing a solvent-soluble masking layer in a first region of a first side of a glass sheet, wherein the surface of the glass sheet is not coated with the masking layer in a second region; then depositing a thin layer stack in the first region and at least a portion of the second region; and then removing the masking layer by washing with the solvent, wherein the masking layer is a discontinuous layer forming a pattern of a two-dimensional network of lines, each line having a width between 0.2 and 2.0 mm.
[0009] The present invention also relates to a window glass obtained by the method, comprising a glass sheet, a first side of which is coated with a thin layer stack, the thin layer stack being discontinuous in a first region and continuous in at least a portion of a second region, wherein in the first region, portions not coated by the thin layer stack form a pattern of a two-dimensional network of lines, each line having a width between 0.2 and 2.0 mm.
[0010] The inventors were able to demonstrate that using a discontinuous masking layer that forms a specific pattern, rather than a continuous masking layer, facilitates and, in particular, accelerates the subsequent removal of the layer. This allows the use of less efficient and therefore cheaper cleaning machines. Other advantages will also be discussed in the remainder of this document.
[0011] The pattern formed by the masking layer consists of a two-dimensional network of lines, referred to herein as a "mesh." Without being bound by any scientific theory, it appears that the presence of these lines increases the possible entry points for the solvent and increases the ratio between the solvent-accessible surface area and the total volume of the masking layer to be removed. This makes cleaning faster and more efficient.
[0012] The solvent is preferably water, so the masking layer is water-soluble. Alternatively, the solvent can be an organic solvent, such as an alcohol.
[0013] A two-dimensional network of lines creates a negative network of separated regions without a masking layer. After the masking layer is removed, these regions remain coated with a thin stack of bodies. In the negative image, a two-dimensional network of lines without stacking bodies is formed. However, it turns out that the successive lines, because of their continuity, block the passage of moisture from the edges of the window glass, thus preventing corrosion. The two-dimensional nature of the lines prevents this passage in two directions on the window glass. Using a grid (i.e., using both the two-dimensional properties of lines and patterns) means it is impossible to traverse the first region without encountering lines without stacking bodies. This prevents edge corrosion.
[0014] The first region preferably includes an area intended to be located around the perimeter of the window glass in order to protect the edges of the window glass, through which corrosion can begin and spread.
[0015] The presence of areas still coated by the stacked material when it is deposited on an enamel layer provides additional advantages.
[0016] It is known to deposit an enamel layer in an area specifically called the enamel zone, which is intended to be located around the perimeter of the final window glass. The enamel is typically opaque and black, used to conceal and protect the joints where the window glass is mounted in the vehicle body window opening, as well as the connectors for various sensors used where applicable.
[0017] Enamel is a mineral layer formed by printing a fluid enamel composition comprising glass frit, pigments, and an organic medium (resin and solvent). After enamel firing, the organic medium is removed and the glass frit melts and adheres to the glass sheet to form an enamel layer composed of pigment particles in a vitreous or glass-ceramic binder.
[0018] When glass sheets are bent (as is often the case with automotive window glass), enamel can adhere to the bending tool or another glass sheet (in the case of laminated windows and when two glass sheets to be laminated are bent together). Enamels known to be unlikely to adhere are typically due to the formation of refractory crystals during firing (as a result of glass frit devitrification). However, this "non-stick" enamel is difficult to reconstitute with a configuration where a thin-layer stack is deposited on top of the enamel. The presence of these crystals increases the roughness of the enamel, which in turn reduces the quality of the overlying stack.
[0019] In this case, it has been proven that the presence of areas on the enamel still coated by the stacked body prevents the aforementioned adhesion, and therefore allows the use of enamel without "anti-stick" properties. Furthermore, the presence of areas on the enamel still coated by the stacked body reduces optical distortion in the boundary region between the enamel and the stacked body. This appears to be due to a reduced emissivity difference between the enamel-coated areas that absorb infrared radiation and the stacked body-coated areas that reflect infrared radiation, which in turn leads to a reduced temperature gradient experienced during bending.
[0020] Therefore, and preferably, the method is as follows: before depositing the masking layer, a first side of the glass sheet is coated with an enamel layer in an enamel region, and at least a portion of a first region is located within the enamel region. Thus, the window glass preferably includes an enamel layer in an enamel region, a thin-layer stack is deposited on the enamel layer, and at least a portion of the first region is located within the enamel region. The first region may be entirely located within the enamel region.
[0021] Preferably, the enamel area is an area intended to be located around the perimeter of the final window glass. In the final window glass, this area preferably forms a strip around the perimeter of the window glass, particularly a peripheral strip extending 3 to 25 cm in length from the edge of the window glass. This distance can vary depending on the positioning. In this case, the first area preferably includes an area intended to be located around the perimeter of the window glass, i.e., around the enamel area, preferably in the form of a peripheral strip extending 0.4 to 5 cm or 0.6 to 4 cm in length from the edge of the window glass.
[0022] The lines preferably have a width between 0.3 and 1.0 mm, particularly between 0.4 and 0.8 mm. It is difficult to apply very narrow lines using printing techniques such as digital printing or screen printing. Furthermore, a very narrow width may be insufficient to prevent moisture from passing through.
[0023] Lines can take any shape. In particular, they can be straight lines. Lines can intersect at any possible angle, such as 90°. When straight lines intersect at right angles, the grid is a square grid, and the areas in the final window glass still coated by the stacked volume are rectangular or square. The shape and size of these areas are controlled by the distance between the lines.
[0024] The distance between the lines is preferably between 1 and 10 mm, particularly between 2 and 5 mm. The distance between the lines and the width of the lines can be used to adjust the coverage of the masking layer over the first region, i.e., the percentage of the surface area of the first region occupied by the total surface area of the lines.
[0025] The total surface area of the lines preferably occupies 10% to 50% of the surface area of the first region. This coverage is preferably between 15% and 40%, particularly between 20% and 35%. The area of the first region is determined by considering the minimum area surrounding the entire masking layer. When the masking layer is deposited in several discontinuous regions, the first region itself can consist of several basic regions. Excessive coverage may cause enamel adhesion. Insufficient coverage may reduce corrosion resistance. The first region preferably occupies 1% to 10% of the glass sheet surface.
[0026] The glass sheet is typically soda-lime silicate glass, but other glasses, such as borosilicates or aluminosilicates, can also be used. The glass sheet is preferably obtained by the float glass process, i.e., by casting molten glass onto a bath of molten tin. The glass sheet can be clear glass or colored glass, for example, colored green, blue, gray, or bronze. For this purpose, the chemical composition of the first glass sheet advantageously includes iron oxide in a weight range of 0.5% to 2%. It may also contain other colorants, such as cobalt oxide, chromium oxide, nickel oxide, erbium oxide, or selenium. The glass sheet preferably has a thickness in the range of 0.7 to 19 mm, particularly 1 to 10 mm, particularly 2 to 6 mm, or 2 to 4 mm.
[0027] As previously mentioned, the method may include depositing an enamel layer prior to depositing a masking layer. This deposition is preferably produced by screen printing or digital printing, particularly by inkjet printing. For screen printing, a screen printing stencil is placed on a glass sheet containing mesh openings, some of which are blocked. An enamel composition is then deposited onto the stencil, and a squeegee is used to force the enamel composition through the stencil in areas where the mesh openings are not blocked, thereby forming a wet enamel layer.
[0028] The enamel composition preferably comprises at least a glass frit, a pigment, and an organic medium. The organic medium preferably comprises a resin and a solvent. The pigment preferably comprises one or more oxides selected from oxides of chromium, copper, iron, manganese, cobalt, and nickel. These may be, for example, chromates of copper and / or iron. The glass frit is preferably bismuth borosilicate and / or zinc borosilicate. The frit composition is preferably suitable for obtaining a low-roughness enamel layer, reducing the softening temperature of the frit, and reducing the risk of devitrification. Suitable enamel compositions are described, for example, in application WO2022 / 225391.
[0029] Then dry the wet enamel layer, especially using infrared or ultraviolet radiation.
[0030] Preferably, the enamel layer then undergoes a pre-firing process before the application of the masking layer. This process is preferably carried out in a temperature range of 300 to 600°C, particularly 400 to 550°C.
[0031] The enamel area preferably occupies 2% to 25% of the surface area of the glass sheet or the final window glass, particularly 3% to 20%, or 5% to 15%.
[0032] Preferably, the enamel layer is in direct contact with the glass sheet, and the masking layer is in direct contact with the enamel layer.
[0033] The enamel layer preferably has a roughness Ra of up to 2.0 µm, particularly between 0.1 and 1.0 µm or between 0.1 and 0.7 µm. The roughness Rz preferably does not exceed 5 µm.
[0034] Preferably, the cleaning is performed before applying the masking layer.
[0035] The masking layer is preferably applied by digital printing, particularly inkjet printing or screen printing. These techniques enable the application of the fluid composition in a predetermined pattern. Digital printing is preferred.
[0036] Inkjet printing is preferably performed using a printhead whose movement (particularly its position and speed) is computer-controlled, or using a series of stationary printheads through which the glass sheet faces and passes at a controlled speed. For this purpose, said or each printhead includes a nozzle through which ink droplets are locally projected onto the glass sheet. This technique is sometimes referred to as “drop-on-demand” (DOD). Advantageously, the glass frit and pigment have a volumetric particle size distribution such that D90 is at most 2 µm. D90 is determined, for example, by laser particle size analysis. The viscosity of the ink is preferably between 1 and 50 mPa·s.
[0037] The fluid composition preferably comprises an organic medium, particularly a solvent and a resin. It also preferably comprises glass frit.
[0038] The deposition of the masking layer is preferably followed by drying, prior to the deposition of the thin-layer stack. Specifically, drying can be performed using infrared or ultraviolet radiation. In the latter case, the fluid composition preferably comprises a photocrosslinkable resin.
[0039] The masking layer preferably has a thickness of 10 to 60 µm, particularly 15 to 50 µm or 25 to 45 µm.
[0040] Thin-layer stacks are preferably deposited by cathode sputtering, particularly magnetic field-assisted (“magnetron”) sputtering. In this method, plasma is generated in a high vacuum near a target containing the chemical element to be deposited. By bombarding the target, the active species of the plasma tear off the element, which is then deposited onto a glass sheet to form the desired thin layer. When the layer is made of material produced by a chemical reaction between the element torn off the target and a gas contained in the plasma, the method is called a “reactive” method. The main advantage of this method is the possibility of depositing very complex layer stacks, typically in the same apparatus, by sequentially running the glass sheet under each target along a single line.
[0041] The thin-layer stack is preferably deposited over the entire surface area of the glass sheet. The thin-layer stack is preferably in direct contact with the glass sheet in the second region, or in direct contact with the masking layer in the first region (the stack is also in direct contact with the glass sheet in the unpatterned portion of the first region).
[0042] The thin-layer stack preferably comprises at least one functional layer that reflects infrared radiation, particularly selected from a metal layer (especially silver, or niobium, or gold) and a transparent conductive oxide (TCO) layer. The TCO is particularly selected from indium and tin oxide, doped tin oxide (e.g., doped with fluorine or antimony), and doped zinc oxide (e.g., doped with aluminum or gallium). A thin layer is understood to have a thickness typically not exceeding 5 µm, particularly not exceeding 1 µm.
[0043] According to a preferred embodiment, the thin-layer stack comprises at least one silver layer, particularly one, two, three, or four silver layers. The physical thickness of the silver layers, or the sum of the thicknesses of the silver layers where appropriate, is preferably between 2 and 50 nm, particularly between 3 and 40 nm.
[0044] According to another preferred embodiment, the thin-layer stack comprises at least one indium tin oxide layer. Its physical thickness is preferably between 30 and 200 nm, particularly between 40 and 150 nm.
[0045] To protect each of the functional layers (whether metallic or based on transparent conductive oxides), each of these layers is preferably surrounded by at least two dielectric layers. The dielectric layers are preferably based on oxides, nitrides, and / or oxynitrides of at least one element selected from silicon, aluminum, titanium, zinc, zirconium, and tin. The stack may also include barrier layers, such as metal or nitride layers, to protect the functional layers from oxidation.
[0046] The cleaning step is preferably carried out by contacting the glass sheet with a solvent, preferably water, in which the masking layer is soluble. Cleaning can be performed in an industrial cleaning machine, particularly one equipped with brushes.
[0047] The glass sheet can then undergo one or more cutting steps to cut it to dimensions corresponding to the final window glass. This is the case when the steps of depositing the masking layer and thin-layer stack, and optionally the enamel layer, have already been performed on a prototype. Alternatively, when these steps have already been performed on a glass sheet that already has the desired dimensions, no cutting step is required after the deposition step.
[0048] When the thin-layer stack is further designed to provide heating functionality, an electric current supply must be provided. This can be, in particular, by screen-printing strips of silver paste deposited on the thin-layer stack at the two opposite edges of the glass sheet.
[0049] Preferably, after removing the masking layer, the method includes the step of bending the glass sheet. Therefore, the window glass is preferably curved.
[0050] Bending can be done either by gravity (the glass deforms under its own weight) or by pressing at temperatures typically between 550 and 650°C.
[0051] When glass sheets are integrated into a laminated window glazing unit, where one sheet is adhesively bonded to another, the two sheets are preferably bent together. In this case, the glass sheets can be kept separate by placing an interlayer powder between them to ensure a gap of tens of micrometers (typically 20 to 50 µm). The interlayer powder is, for example, based on calcium carbonate and / or magnesium carbonate and is designed to reduce the risk of adhesion between the glass sheets. During bending, the inner glass sheet (intended to be positioned inside the passenger compartment) is typically placed above the outer glass sheet.
[0052] As already mentioned, the method of the present invention prevents the enamel from adhering to the bending tool or another glass sheet because of the area where the stacked body remains above the enamel.
[0053] The window glass according to the present invention can be laminated window glass, wherein a glass sheet is adhesively bonded to another glass sheet through a laminated interlayer.
[0054] The lamination step can be performed in an autoclave, for example, at a temperature of 110 to 160°C and a pressure of 10 to 15 bar. Prior to autoclave treatment, trapped air between the glass sheet and the interlayer can be eliminated by calendering or applying negative pressure.
[0055] The interlayer preferably comprises at least one sheet of polyvinyl acetal, particularly polyvinyl butyral (PVB). The interlayer can be colored or uncolored to adjust the optical or thermal properties of the glazed unit if necessary. The interlayer can advantageously possess acoustically absorbing properties to absorb airborne or structure-borne sound. For this purpose, it can particularly consist of three polymer sheets, including two so-called outer PVB sheets surrounding an inner polymer sheet (optionally made of PVB) having a lower hardness than the outer sheets. The thickness of the interlayer is typically in the range of 0.3 to 1.5 mm, particularly 0.5 to 1 mm. The interlayer can have a smaller thickness at the edges of the window glass than at the center to prevent double images when using a head-up display (HUD).
[0056] The window glass according to the invention is preferably curved. It is preferably curved and laminated. In this case, the thin-layer stack is preferably on surface 2 of the laminated window glass (i.e., in contact with the interlayer of the lamination), and these surfaces are generally numbered from the outside of the window glass. In other words, the first surface of the glass sheet is on surface 2 of the laminated window glass.
[0057] The window glass is preferably the roof or windshield of a motor vehicle, or the rear window of a motor vehicle.
[0058] The following implementation plan and the following Figures 1 to 7The invention is shown in a non-limiting manner.
[0059] [ Figure 1 [ ] is a schematic diagram of the glass sheet before the deposition of the masking layer.
[0060] [ Figure 2 [This is a schematic diagram of the glass sheet after the deposition of the masking layer and the thin-layer stack.]
[0061] [ Figure 3 ]yes[ Figure 2 A magnified view of a portion of the image.
[0062] [ Figure 4 ]yes[ Figure 3 The cross-section of ].
[0063] [ Figure 5 [Illustration of a window glass obtained by the method of the present invention]
[0064] [ Figure 6 ]yes[ Figure 5 A magnified view of a portion of the image.
[0065] [ Figure 7 ]yes[ Figure 6 The cross-section of ].
[0066] [ Figure 1 The figure shows a prototype glass sheet 1, which has a larger size than the final window glass. In this figure, a single glass pane is obtained by cutting this prototype, but other embodiments are also possible, in which several glass panes can be obtained from a single prototype.
[0067] Enamel layer 3 has been deposited on the glass sheet 1 in strip-shaped enamel areas, which are intended to be located around the perimeter of the final window glass after cutting. The enamel layer is deposited, for example, by screen printing. In this example, the enamel layer is opaque and black. Its luminance L*, measured as reflectance, is preferably less than 5.
[0068] [ Figure 2 The image shows the glass sheet 1 after the deposition of the masking layer 5. The latter is deposited on enamel and, around the periphery of the enamel strips 3, at the edge that will become the window glass, is shown in a grid pattern. The entire area of the deposition of the masking layer 5 corresponds to the first region Z1. This is the location where the thin-layer stack is partially removed by removing the masking layer.
[0069] Masking layer 5 in [ Figure 3 The image is enlarged in this figure. In this figure, the enamel layer 3 is shown against a shaded background. The masking layer 5 deposited on the first region Z1 is shown as equidistant straight lines in this example. i 7 iIn the form of a two-dimensional network, these lines intersect at right angles to form separated square regions. Line 6 i 7 i All of these regions have the same width e. For example, the width e is 0.5 mm, and the square region has a side length of 3 mm. The coverage, i.e., the proportion of the total surface area of the lines occupying the first region, is 29%. The second region Z2 is not covered by the masking layer 5. The thin layer stack deposited on the entire first and second regions Z1 and Z2 is not shown in this figure.
[0070] Other variations are of course possible: for example, the lines may not be straight, and / or may not intersect at right angles, and / or may not be equidistant, and / or may not all have the same width.
[0071] [ Figure 3 The cross section of ] is in [ Figure 4 As shown in the diagram. In the first region Z1, a line 7 with a width of e can be seen of the masking layer 5. i And a thin stack 9 deposited in the first and second regions Z1 and Z2. The stack is deposited both in contact with the enamel layer 3 (and outside the enamel region in contact with the glass sheet 1, this portion of the window glass is not shown here), and also with line 6. i 7 i touch.
[0072] Figures 5 to 7 The final window glass is shown after the masking layer 5 has been washed away and the glass sheet 1 has been cut to its final size. Removal of the masking layer removes the underlying thin-layer stack. In the first region Z1, around the periphery of the window glass, the thin-layer stack 9 is therefore discontinuous and includes separated regions 12. i In this case, it is square. In this first region Z1, the portion not covered by the thin-layer stack 9 is formed by lines 10. i 11 i The pattern is composed of a two-dimensional network, and each line has a width of e.
[0073] In one embodiment of the invention, the method is as shown in the figure. A layer of black enamel (Fenzi, 1L5350) without anti-stick properties is deposited on a float glass sheet, and a masking layer (Tecglass FC 1003) is deposited on a portion of the enamel layer at the edge of the window glass. The masking layer forms a grid pattern, wherein the lines have a width of 0.5 mm and are spaced 3 mm apart. After cleaning in a washing machine, the masking layer is completely removed. On the other hand, in a comparative example, where the masking layer forms a continuous, unpatterned layer, the same cleaning process cannot remove the entire masking layer and the overlying stack. Bending tests also revealed adhesion in the area where the stack had been removed in the comparative example, while no adhesion was observed in the embodiment according to the invention.
Claims
1. A method for obtaining window glass, comprising: A solvent-soluble masking layer (5) is deposited in a first region (Z1) on a first side of a glass sheet (1), while the surface of the glass sheet (1) is not coated with the masking layer in a second region (Z2); then a thin stack (9) is deposited in the first region (Z1) and at least a portion of the second region (Z2); then the masking layer (5) is removed by washing with the solvent, wherein the masking layer (5) is a discontinuous layer formed by lines (6) i , 7 i The pattern is composed of a two-dimensional network, and each line has a width (e) between 0.2 and 2.0 mm.
2. The method of claim 1, wherein the first region (Z1) includes a region intended to be located around the perimeter of the window glass.
3. The method according to any one of the preceding claims, wherein, Before the deposition of the masking layer (5), the first side of the glass sheet (1) is coated with an enamel layer (3) in the enamel area, and at least a portion of the first region (Z1) is located in the enamel area.
4. The method according to any one of the preceding claims, wherein, The line (6) i 7 i It has a width between 0.3 and 1.0 mm, especially between 0.4 and 0.8 mm.
5. The method according to any one of the preceding claims, wherein, The line (6) i 7 i ( ) are straight lines that intersect at a 90° angle.
6. The method according to any one of the preceding claims, wherein, The line (6) i 7 i The distance between them is between 1 and 10 mm, especially between 2 and 5 mm.
7. The method according to any one of the preceding claims, wherein, The line (6) i 7 i The total surface area of the first region (Z1) accounts for 10% to 50% of the surface area of the first region (Z1).
8. The method according to any one of the preceding claims, wherein, The masking layer (5) has a thickness of 10 to 60 µm.
9. The method according to any one of the preceding claims, wherein, The masking layer (5) is deposited by digital printing or screen printing.
10. The method according to any one of the preceding claims, wherein, The thin-layer stack (9) is deposited by cathode sputtering.
11. The method according to any one of the preceding claims, wherein, The thin-layer stack (9) includes at least one functional layer that reflects infrared radiation, particularly selected from metal layers and transparent conductive oxide layers.
12. The method according to any one of the preceding claims, wherein, The solvent is water.
13. The method according to any one of the preceding claims further includes the step of bending the glass sheet (1) after removing the masking layer (5).
14. A window glass obtained by the method according to any one of the preceding claims, comprising a glass sheet (1) having a first surface coated with a thin layer stack (9), said thin layer stack being discontinuous in a first region (Z1) and continuous in at least a portion of a second region (Z2), wherein, In the first region (Z1), the portion not coated by the thin-layer stack (9) is formed by lines (10). i ,11 i The pattern is composed of a two-dimensional network, and each line has a width (e) between 0.2 and 2.0 mm.
15. The window glass according to the preceding claim, comprising an enamel layer (3) in an enamel region, a thin-layer stack (9) deposited on the enamel layer (3), and at least a portion of a first region (Z1) located in the enamel region.
Citation Information
Patent Citations
Enamel paste compositions, enamel coated products, and methods of manufacturing the same
WO2022225391A1